(untitled) (KMC Journal, 2023)
Nepal Government’s social security plan has been implementing senior citizens’ Social Security Allowance (SSA) for citizens 68 years old and above. SSA leaves a huge space for the newly certified senior citizens (60 years old) and cutting them off eight years sooner from their daily economic earnings—additionally, the allocated amount of monthly NPR. 4,000 may not cover all their expenses. This research is a continuous search for knowledge about the senior citizens’ status on their social security and their opinion on their use of SSA. Jorpati Older People Association in Kathmandu was chosen as a study area, with the research question focusing on the justifiability of SSA and its purpose. 42.42% of the respondents said that SSA money only complements their social and financial needs. The monthly income from SSA and tenants’ fees goes into the domestic expenses (54.54% of the respondents receiving SSA), thus showing that although the elderly are rendered economically inactive from gaining income or being productive, they continue to be financially responsible for their house and family. The opinion on the requirement of high SSA is directly proportional to their poor economic standing and their participation in their domestic expenses in the family.